Virgin olive oil yield as affected by physicochemical talc properties and dosage. Issue 1 (4th August 2016) - Sadkaoui, Abir; Jiménez, Antonio; Aguilera, Maria P.; Pacheco, Rafael; Beltrán, Gabriel
Abstract : The aim of this work was to assess the effect of physicochemical characteristics of micronized natural talc (MNT) and its dosage on the industrial oil yield (IY) during virgin olive oil (VOO) extraction of Hojiblanca fruits. For this purpose, laboratory scale experiments were performed testing four commercial MNTs differing in their particle size (D50) and carbonate rate at doses ranging from 0 to 3%. The most efficient MNT was characterized by the highest carbonate rate and the lowest particle size achieving the highest improvement of the IY for a dose of 2%. It was also found that the effect of particles size and carbonate rate depends on the MNT dose, being much more pronounced at lower doses and that the use of MNTs with low carbonate levels or high particle size could be compensated using higher doses of talc. Practical applications: This study provides deeper insights into the clarification of the effect of the addition of different doses of MNT, with different physicochemical characteristics on oil yield of Hojiblanca olive fruits. The information contained in this study should be taken into account to choose the suitable MNT dose considering its physicochemical characteristics in order to improve the oil yield for the so‐called difficult pastes. Physical and chemical characteristics of talc affect VOO yield. Abstract : Physical and chemical characteristics of talc affect VOO yield.